Injection of Dicyandiamide‐Treated Pig Slurry Reduced Ammonia Volatilization without Enhancing Soil Nitrous Oxide Emissions from No‐Till Corn in Southern Brazil. Issue 3 (1st May 2014) - Aita, Celso; Gonzatto, Rogério; Miola, Ezequiel C. C.; dos Santos, Daniela B.; Rochette, Philippe; Angers, Denis A.; Chantigny, Martin H.; Pujol, Stefen B.; Giacomini, Diego A.; Giacomini, Sandro J.
Abstract : There is a lack of information on how placement in soil and nitrification inhibitors affects nitrous oxide (N2 O) and ammonia (NH3 ) emissions from pig slurry (PS) applied under no‐till (NT) conditions. Our objective was to determine the impact of injecting PS and treating it with the nitrification inhibitor dicyandiamide (DCD) on NH3 and N2 O emissions from soils under NT in subtropical southern Brazil. The emissions of these gases were compared for shallow (∼ 10 cm) injection and surface broadcasting of PS with and without DCD (8.1–10.0 kg ha −1 ; 6.5–8.4% of applied NH4 –N). Measurements were made at two sites during two summer growing seasons under NT corn crops. Injection reduced NH3 volatilization by 70% but increased N2 O emissions 2.4‐fold (from 2628 to 6198 g N2 O N ha −1 ) compared with surface broadcast application. Adding DCD to PS inhibited nitrification and reduced N2 O emissions by an average of 28% (730 g N2 O–N ha −1 ) for surface broadcast and 66% (4105 g N2 O–N ha −1 ) for injection but did not increase NH3 volatilization. Consequently, N2 O emission factors were much higher for injection (3.6%) than for surface broadcast (1.3%) application and were reduced (0.9%) when DCD was added to injected PS. In conclusion, the injection of DCD‐treated slurry is a recommendable practice for reducing NH3 and N2 O emissions when applying PS on NT corn in southern Brazil.